Synthesis and Characterization of Azo Aromatic Diacyl Chlorides - Yan Qiu, Ming; Chang Zhang, Ji; Yun Shi, Wei; Chao Jia, Qing; Sheng Niu, Yong (Asian Journal of Chemistry, 2012)
A convenient and rapid method for the synthesis of azo aromatic diacyl chlorides has been developed. Eight azo aromatic diacyl chlorides have been synthesized from aromatic nitro acids by using xylene as solvent. Most reaction periods are less than 2 h and the products are obtained in excellent yields with high purity.